2018
DOI: 10.14740/jocmr3636
|View full text |Cite
|
Sign up to set email alerts
|

APACHE II Death Risk and Length of Stay in the ICU Are Associated With Pressure Injury in Critically Ill Patients

Abstract: BackgroundThe aim of this study was to identify factors associated with pressure injury (PI) occurrence in critically ill patients. This was a retrospective cohort study conducted at a mixed intensive care unit (ICU).MethodsUnivariate analysis and logistic regression were used to identify which variables are associated with PI.ResultsTwenty-one (15%) of 142 patients developed PI. The median and the range of the variables in the groups without and with PI were as follows: Braden scale risk score, 13 (8 - 20) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…40 Identification and mitigation of risk becomes paramount. Older age, premorbid conditions, high illness severity, 12 derangements of organ function, 14 invasive interventions, and the attendant immobility characteristic of treating critical illness (e.g., prone positioning, CRRT 22 ) may amplify the risk of SF. 4,9,18,41,42 BMI at either extreme (19 > BMI < 40) has been associated with high risk of SF related to bony prominences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Identification and mitigation of risk becomes paramount. Older age, premorbid conditions, high illness severity, 12 derangements of organ function, 14 invasive interventions, and the attendant immobility characteristic of treating critical illness (e.g., prone positioning, CRRT 22 ) may amplify the risk of SF. 4,9,18,41,42 BMI at either extreme (19 > BMI < 40) has been associated with high risk of SF related to bony prominences.…”
Section: Discussionmentioning
confidence: 99%
“…Multifactorial historic risk factors include patients’ premorbid state of health, physiologic stressors, organ dysfunction, 4,9,10 and increased survivability of catastrophic illness through advances in the delivery of life-sustaining care. 11 Critically ill patient characteristics implicated in the development of SF include high severity of illness, 12 immobility, 13 organ dysfunction, 14 and receipt of any of numerous organ-support modalities, including mechanical ventilation- often with neuromuscular blockade, 4,15 vasopressor therapy, 16,17 or renal replacement therapy (RRT). 18…”
mentioning
confidence: 99%
“…A higher score means a higher risk of death [ 23 ]. Previous studies have shown that the APACHE II risk of death determination is associated with the incidence of PI in critically ill patients [ 24 ]. The present study found that the APACHE II score was an independent risk factor for the occurrence of PI in critically ill patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not collect the data of the APACHE II score as a confounding variable for the relationship between the PRFM and the development of pressure injuries. However, the influence of the APACHE II score on the development of pressure injuries is inconsistent based on existing evidence [ 61 , 62 ]. We included the Braden score in the analysis, which is more widely and consistently used as a significant predictor of pressure injuries [ 34 ].…”
Section: Discussionmentioning
confidence: 99%